Beyond the Needle: Unmasking Atypical Mycobacteria in Postvaccination Abscesses in Children - Amar Shah; Devesh N. Joshi; Anirudh Shah (Wolters Kluwer Medknow Publications, 2024)
Introduction: Atypical or nontuberculous mycobacteria (NTM) are an environmental organism responsible for opportunistic infection. Rapid-growing NTM are more commonly associated with hospital-acquired infections. Many of the organisms responsible for diseases in immunocompromised patients and hospital-acquired infections originate from tap water, such as Mycobacterium kansasii, Mycobacterium xenopi, Mycobacterium gordonae, Mycobacterium simiae, Mycobacterium mucogenicum, Mycobacterium fortuitum, Mycobacterium chelonae, and Mycobacterium abscessus. NTM is a rare organism responsible for the injection abscess. Considering low incidents, not much clinical data are available for this condition. Here, we discuss such cases which can be helpful to spread awareness and provide data for future policy makers. Materials and Methods: This was a retrospective study. Data on patients with injection abscess were collected from the last 6 years. Detailed history and clinical examination findings were analyzed. Children with injection abscess were operated and their further management and outcome were studied. Results: A total of 13 cases with confirmed culture of NTM were treated over 6 years. The age ranged from 2½ months to 5¾ years with male:female ratio of 7:6. All patients hailed from the same geographical area. All children were healthy with no history of any long-term or chronic illness, without additional symptoms and had received Bacillus Calmette-Guérin vaccination at birth. The total duration of illness varied from 1 to 5 months, with a mean of 3 months. All patients had a history of intramuscular age-appropriate vaccination as per the national immunization schedule. All patients were followed up to 6 months after intervention and none of our patients developed relapse. Conclusion: Patient who does not respond with optimum treatment should have a high suspicion of such opportunistic infection, which is crucial to their management. Hospital-acquired NTM infections often result from contaminated instruments or fluids. Adherence to strict aseptic precautions, hand hygiene and environmental precautions are the key to preventing these infections. In case of skin and soft tissue infections / abscesses, surgical intervention plays a significant role for managing the patient.